Biotransformation of Indigo Pigment by Indigenously Isolated Pseudomonas sp. HAV-1 and Assessment of Its Antioxidant Property. (17th November 2014) - Dua, Aditi; Chauhan, Kishor; Pathak, Hilor
Abstract : Chemical synthesis of indigo poses harsh environmental hazards and adverse human health effects. This necessitates an environment-friendly and producer-friendly approach for indigo production. The present study was thus significant as it reports an indigenously isolated potential indigo pigment producing culture identified as Pseudomonas sp. HAV-1 with noteworthy antioxidant property. The bioindigo pigment was characterized using various analytical techniques. The pigment production was enhanced from 412  μ g mL −1 to 700  μ g mL −1 by optimizing the growth parameters. Furthermore, the antioxidant property of indigo pigment is hitherto unexplored. This property can significantly append to its therapeutic potential. The bioindigo pigment produced by Pseudomonas sp. HAV-1 depicted 2.2  μ M ascorbic acid equivalent antioxidant property. More to the point, the present work addresses a footstep towards green production of indigo.